Imposing Additional Criminal Dismissals Against Military Who Commit Crimes of Domestic Violence - Budhi, Reza Santya; Prastopo, Prastopo; Edwin, Edwin (CV. Rayyan Dwi Bharata, 2025)
Domestic violence (KDRT) is a serious social issue, including within the Indonesian military. Cases of domestic violence committed by military personnel not only affect the victims but also impact the overall reputation of the military institution. This study aims to analyze the handling of domestic violence cases by military personnel and to explore the process of imposing additional criminal penalties in the form of dismissal for offenders within the military environment. Using a normative juridical research method, this study focuses on the application of laws in Indonesia, particularly Law Number 23 of 2004 on the Elimination of Domestic Violence and Law Number 25 of 2014 on Military Discipline.The research findings indicate that handling domestic violence cases in the military poses unique challenges due to the duality of legal systems between general criminal law and military discipline law. In addition, there are social barriers such as stigma against victims and fear that hinder case disclosure. The imposition of additional criminal penalties, such as dismissal, serves as a key sanction to maintain military integrity and discipline, where the dismissal is aimed at creating a deterrent effect and protecting the victim. The dismissal process not only encompasses aspects of criminal law but also involves formal and hierarchical internal military mechanisms.This study highlights the need for reform in the military justice system, particularly in addressing domestic violence cases, and emphasizes the importance of raising awareness and providing support to victims of domestic violence within military families. Strengthening legal protection and applying strict sanctions are expected to reduce the incidence of domestic violence in the military environment and improve justice for victims.